2019
DOI: 10.3390/ijms20205053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ABCA4 Deep-Intronic Variants and Related Phenotype in An Unsolved “One-Hit” Cohort with Stargardt Disease

Abstract: We investigated the prevalence of reported deep-intronic variants in a French cohort of 70 patients with Stargardt disease harboring a monoallelic pathogenic variant on the exonic regions of ABCA4. Direct Sanger sequencing of selected intronic regions of ABCA4 was conducted. Complete phenotypic analysis and correlation with the genotype was performed in case a known intronic pathogenic variant was identified. All other variants found on the analyzed sequences were queried for minor allele frequency and possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 58 publications
(87 reference statements)
1
28
0
Order By: Relevance
“…In addition, a recent study on deep-intronic ABCA4 variants in a French cohort also concluded that the c.5196+1137G>A variant was mostly associated with a milder phenotype, based on six subjects harboring this allele. 32 It should also be noted, however, that evidence is emerging that some variants that were long considered pathogenic or benign by themselves, such as c.2588G>C; p.[G863A,G863del] and c.5603A>T; p.(N1868I), are fully penetrant only when in combination on the same allele. The same is true for the cis configuration of p.(N1868I) with a recently identified intronic mutation, c.769-784C>T. 9 , 33 , 34 In addition, modifier variants, either within or outside of ABCA4 , as well as environmental factors will likely play a role in determining disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study on deep-intronic ABCA4 variants in a French cohort also concluded that the c.5196+1137G>A variant was mostly associated with a milder phenotype, based on six subjects harboring this allele. 32 It should also be noted, however, that evidence is emerging that some variants that were long considered pathogenic or benign by themselves, such as c.2588G>C; p.[G863A,G863del] and c.5603A>T; p.(N1868I), are fully penetrant only when in combination on the same allele. The same is true for the cis configuration of p.(N1868I) with a recently identified intronic mutation, c.769-784C>T. 9 , 33 , 34 In addition, modifier variants, either within or outside of ABCA4 , as well as environmental factors will likely play a role in determining disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A step further in genetic diagnosis has been attained when deep-intronic variants that alter the splicing pattern have been identified, as is the case in Stargardt disease, a macular disorder with a very well defined clinical phenotype and a major causative gene, ABCA4. In fact, the introduction of the whole ABCA4 locus in the target NGS panels clearly helps to increase the genetic yield in Stargardt disease patients [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…There is a clustering of different deep-intronic variants in introns 7 (n = 4), 13 (n = 4), 30 (n = 6) and 36 (n = 4). The total number of alleles carrying deep-intronic and near-exon variants is 355 ( Table 4 ) ( Bauwens et al, 2015 ; Bauwens et al, 2019 ; Bax et al, 2015 ; Braun et al, 2013 ; Khan et al (2020) ; Khan et al, 2019 ; Nassisi et al, 2019 ; Sangermano et al., 2019 ; Schulz et al, 2017 ; Zernant et al, 2018 ; Zernant et al, 2014b ). Only seven variants were found in more than 10 alleles, i.e.…”
Section: Abca4 Pre-mrna Splicing Defectsmentioning
confidence: 99%